The Consumption of Renewable Energy Sources (RES) by the European Union Households between 2004 and 2019 - Piekut, Marlena (Energies (Basel), 2021)
The paper provides the analysis of fuel and energy transition in households sector and its sustainable development in the period 2004–2019. The main purpose of the paper is to determine the development trends in the use of renewable energy sources (RES) in the EU countries household sector in 2004–2019, to recognize the state of development and functioning of the studied area as well as to indicate their successes and shortcomings in observed reality. The article employs the results of Energy balance sheets from Eurostat. The research entity were households from 28 European Union countries, with particular emphasis on households from Poland and selected neighboring countries. The research subjects there were different sources of renewable energy used by households, i.e., solar thermal system, geothermal technologies, primary solid biofuels, charcoal, biogases, blended biogasoline, blended biodiesels, ambient heat (heat pumps). To achieve the research objective a number of statistical measures ands methods, including cluster analysis and linear trend indicator applied. In the analyzed 16 years, an absolute and relative increase in the use of RES in the household sector was noticed. Taking into account the specificity of using RES in households, 6 clusters of countries were distinguished. In Poland, it was noted that there was a significant increase in the use of RES in households, with stagnation in the use of non-renewable energy sources, such as, for example, hard coal.